Profile of Meaningful Learning in Mathematics among Elementary School Students on Number and Operations Topics - Yonathan S Pasinggi (International Journal of Education, Culture, and Society, 2026)
Meaningful learning is a crucial aspect of elementary mathematics instruction, particularly in number and operations topics, which serve as the foundation for further mathematical understanding. However, mathematics learning in elementary schools still tends to emphasize procedural skills and provides limited opportunities for students to connect mathematical concepts with real-life contexts, resulting in less meaningful understanding. This study aims to analyze the profile of meaningful learning in mathematics among elementary school students on number and operations topics. A descriptive method with a qualitative approach supported by quantitative data was employed. The research was conducted at SDN 50 Bonto Panno, Pangkep Regency, during October–November 2025, involving 25 fifth-grade students as research subjects. Data were collected through contextual-based tests on number and operations, a meaningful learning questionnaire, classroom observations, and documentation of students’ work. Data were analyzed by categorizing students’ meaningful learning based on indicators of conceptual understanding, connections to real-life experiences, and the ability to explain and reflect on mathematical concepts. The findings indicate that students’ meaningful learning in mathematics was generally at a moderate level. Students demonstrated adequate procedural understanding of number operations but experienced difficulties in connecting mathematical concepts to contextual situations and verbally explaining the meaning of the concepts learned. These findings suggest that meaningful learning in elementary mathematics requires stronger integration of contextual, reflective, and student-centered instructional practices. This study contributes to elementary mathematics education by providing empirical insight into students’ meaningful learning profiles and highlighting the need to improve instructional strategies that support conceptual understanding in number and operations topics.